Effects of internal conflicts on productivity of arable crop farmers in Oyo State, Nigeria (Agriculture, Food, and Natural Resources Journal, 2024)
Internal unrest has an impact on agricultural production, especially in the rural communities that are the food production sites in Nigeria. Recently, communities in Oyo State of Nigeria have been witnessing increasing farmer-herder clashes, affecting food crop production. Hence, this study analyzed the effects of conflicts on the productivity of arable farmers in Oyo State, Nigeria. With primary data obtained from two hundred and twenty-three (223) randomly sampled respondents for two time periods (pre-planting and post-planting of 2022/2023), the data were analyzed with both descriptive statistics (such as frequency and percentage) and the Ordinary Least Square (OLS) model. The results showed that about 45.29% of the respondents’ experienced farmer-herder crises within the last production cycle, 13% claimed families’ land disputes, and only 4.93% claimed inter-border conflict in their area. Furthermore, herders’ encroachment, land disputes, and labour reduce farmers’ productivity significantly at 5% and 1% levels, respectively. Conversely, the coefficients of marital status, membership of organisation and access to extension service showed significance at 10% level, while education and farm size showed significance at 5% level, an indication of positive influence on the productivity of arable farmers in the study area. In conclusion, the increasing farmer-herder conflict reduces arable crop production through the displacement of farmers and loss of interest in production, which will invariably lead to the migration of young men in agriculture.
Keywords: Boundary; Encroachment; Farmer-Herder; Grazing; Post-Planting